Gambaran Pengasuhan Orang Tua di Suku Nias - Lase, Dhea Marselena; Rusli, Devi (YASIN, 2024)
Parents are the primary and first educators of children within a family. In the process of emotional adjustment for children, this cannot be separated from family support. Communication is the key to relationships within a family. The parenting style of the Nias ethnic group has its own uniqueness influenced by local culture and values. According to Vinden (2001), there are two parenting styles: authoritarian and authoritative. This study aims to describe the parenting practices of the Nias ethnic group. The research employs a quantitative method using descriptive statistical analysis. The population for this study consists of parents in the Nias ethnic group, with a total of 60 subjects. The sampling technique used is purposive sampling. This study utilizes the parenting style scale developed by Vinden, which has been modified by O'Reily and Peterson (2014) and adapted into Indonesian by Hasanah and Rusli (2020). Based on the research results, the mean for authoritarian parenting style is 18.9 with a standard deviation of 1.50, while the mean for authoritative parenting style is 10.3 with a standard deviation of 1.84. This indicates that the authoritarian parenting style among parents in the Nias ethnic group is higher.